FACTORS RELATED TO EXCLUSIVE BREASTFEEDING FOR BABIES IN PUSKESMAS 23 ILIR, PALEMBANG - Sakemti Putri; Chairil Zaman; Dianita Ekawati (Majalah Kedokteran Sriwijaya, 2022)
Lack of breast milk intake results in an imbalanced baby's nutritional needs. This study aims to determine the factors related to exclusive breastfeeding for infants in the work area of Puskesmas 23 Ilir. This research is an analytic survey with a cross sectional design. This research was conducted at Puskesmas 23 Ilir. The population in this study were 229 mothers who had babies aged 6 months and the research sample was 70 mothers. The results showed that the majority of exclusive breastfeeding gave exclusive breastfeeding amounted to 46 respondents (56.7%), and 24 respondents (34.3%) did not provide exclusive breastfeeding. The chi square test of the association between knowledge (p value = 0.014), attitude (p value = 0.039), mother occupation (p value = 0.045), family support (p value = 0.042), nutritional status of mothers (p value= 0.08). The dominant factor in this study was the variable of mother's attitude with a value of ? = 0.007 and (Exp B = 7.844). It is recommended to provide education to the public for health workers to be able to provide information and education about exclusive breastfeeding to mothers.